Tilt response of pyranometers - studies at Pune - KANADE, V. V.; ABHYANKAR, V.V. (MAUSAM, 1997)
ABSTRACT. Pyranometers are normally used in a horizontal position to measure the global solar irradiance from the sun and sky. Because of the use of the pyranometers at sloping angles for determining the efficiency of the solar energy conversion installations, the effect of the tilled positions have to be quantified. Central Radiation Laboratory at Pune has made its own device and made measurements of the outputs of different pyranometers at different sloping angles. The results are discussed in the paper.